EFEKTIVITAS METODE DRILL TERHADAP HASIL BELAJAR DALAM KETERAMPILAN MENULIS TEGAK BERSAMBUNG PADA TEMA 6 MERAWAT HEWAN DAN TUMBUHAN SUBTEMA 4 MERAWAT TUMBUHAN PESERTA DIDIK KELAS II SDN 2 KEDUNGGEBANG BANYUWANGI - Silvia Indriati; Hari Satrijono; Fitria Kurniasih (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to determine the effectiveness of the drill method on learning outcomes in cursive writing skills on theme 6 caring for animals and plants, sub-theme 4 caring for plants for second grade students of SDN 2 Kedunggebang Banyuwangi. This study used a quasi-experimental study with a non-equivalent control group research design. The research subjects were class IIA and class II B at SDN 2 Kedunggebang. Based on the results of research analyzed with the help of SPSS version 25, it shows that there is an effectiveness of the drill method on learning outcomes in cursive writing skills on theme 6 caring for animals and plants sub-theme 4 caring for plants for second grade students at SDN 2 Kedunggebang Banyuwangi as evidenced by tcount > ttable (5,453 >1,690). While the calculation of the relative effectiveness test was obtained at 57.48% and included in the category of moderate effectiveness.